2013
DOI: 10.1111/ijcp.12245
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 as a predictor of cardiovascular events in troponin-negative non-ST elevation acute coronary syndrome patients

Abstract: Interleukin-6 is an independent predictor of adverse events in low-moderate risk patients with NSTE-ACS and troponin-negative. Its use identifies a higher risk population in moderate-risk patients. This provides together with history of IHD a better discrimination and reclassification beyond that achieved with clinical risk variables from TIMI risk score in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 39 publications
0
9
0
2
Order By: Relevance
“…In this process, inflammation is thought to play a key role along with several other risk factors 33 . Previous investigations have shown that a high level of IL-6 is an independent predictor of adverse events in patients with ACS 34 . Our data showed that the presence of the D allele is related to higher IL-6, with 18.6 ng/ml in DD and 18.0 ng/ml in ID versus 14.7 ng/ml with the II genotype 15 .…”
Section: Discussionmentioning
confidence: 93%
“…In this process, inflammation is thought to play a key role along with several other risk factors 33 . Previous investigations have shown that a high level of IL-6 is an independent predictor of adverse events in patients with ACS 34 . Our data showed that the presence of the D allele is related to higher IL-6, with 18.6 ng/ml in DD and 18.0 ng/ml in ID versus 14.7 ng/ml with the II genotype 15 .…”
Section: Discussionmentioning
confidence: 93%
“…Wang et al 55 found that IL-6 was related to the procession of ACS and had prognostic use. Serum IL-6 was shown to be useful for predicting mortality in patients with ACS51 and identifying individuals who could benefit from targeted interventional or intensive therapy 56. However, the circadian fluctuation in IL-6 levels and a lack of confirmatory studies have limited the use of IL-6 as an effective biomarker of ACS 57.…”
Section: Summary Of Cardiac Biomarkersmentioning
confidence: 99%
“…Inflammation plays an important role in the progression and destabilisation of ACS. Several inflammatory biomarkers, such as interleukin-6 [2], C-reactive protein [3], and matrix metalloproteinases [4], have been identified as independent predictors of adverse outcomes in patients with ACS. However, these biomarkers are not used as routine or inexpensive examinations for patients with ACS.…”
Section: Introductionmentioning
confidence: 99%